Beyond COVID‐19: Reported clinical practices in maternity care in Victoria during the COVID‐19 pandemic and implications for the future – A statewide review - Forster, Della A.; Hyde, Rebecca; Matthews, Robyn; Benzie, Charlie A. (Australian & New Zealand journal of obstetrics & gynaecology, 2025)
Background In Australia, during the COVID‐19 pandemic many routine pregnancy visits were replaced by telehealth, along with changes to routine screening and visitor policies. Many providers plan to continue these changes. Aims Describe changes to maternity care provision across the state of Victoria during the COVID‐19 pandemic. Materials and Methods A population‐based cross‐sectional design was used. Managers of maternity services (public and private) were invited to complete a questionnaire by telephone or online exploring changes to care delivery, telehealth practices, perceived impact of changes and future telehealth implementation. Results Fifty per cent of maternity service managers (34/68; 27 public, six private) responded (March–April 2021). Around 50% of all pregnancy visits became telehealth, with multiple combinations of face‐to‐face and telehealth visits; 92% conducted the first (booking) appointment via telehealth. No specific gestational visit was conducted face‐to‐face by all services. Visits most likely to be face‐to‐face were at 39 and 40 weeks gestation (65%). For telehealth appointments, there was an ad hoc approach to routine screening, eg, measuring blood pressure (11% did not advise at all), fetal growth (26%—no specific strategy) and fetal heart rate (15%—no specific strategy). Over half (52%) would consider maintaining telehealth post‐pandemic. Conclusions Even in a single state, there was great variation in what constitutes telehealth, when pregnant women should have face‐to‐face visits, and what routine screening in pregnancy should be maintained. This is concerning given over half the services are planning to continue telehealth post‐pandemic, despite the lack of evidence of safety, efficacy and input from women and clinicians.